HPLC Method for Characterisation of Carbohydrates in Fresh and Processed Fruit Juices - P. Sharma, Gyan; Chakraborti, I.; P. Tyagi, Bijender; Raghav, S.S.; Sarin, R.K. (Asian Journal of Chemistry, 2010)
Estimation and characterisation of glucose, fructose, sucrose, maltose and lactose by high performance liquid chromatography (HPCL) was performed in fruit juices in both fresh and processed forms. Following extraction, HPLC analysis took approximately 17 min for complete analysis. A good recovery was also obtained from a variety of fruit juices. The method suggests an update of available carbohydrate literature quanytatively in Indian and international fruit products.